THE ESTABLISHMENT OF THE ARABIC LEARNING ENVIRONMENT IN ISLAMIC HIGHER EDUCATION INSTITUTION IN NORTH SUMATERA - Sahkholid Nasution; Zulheddi Zulheddi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
This study aims to highlight the establishment of supporting environment to Arabic learning in some PTKIs (Islamic Higher Education Institutions) in North Sumatera Indonesia. It could be contended that the supporting environment to Arabic learning could enhance the quality of learning the language itself. Concerning some challenges in teaching and learning Arabic as a foreign or second language, one of major strategies which could be applied is to establish the supportive learning environment which could facilitate the process of learning the language becoming more attractive and optimizing. This study is conducted by qualitative approach which the data were obtained from series of observations, interviews, and documentations. The result of this study depicts that there are some key factors which could conform the establishment of supportive environment to the teaching and learning Arabic in those Islamic Institutions and also the level of language understanding which could be endorsed by how established the environment itself.